(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the poetics of the postmodern text as a distinct system of artistic principles shaping the specificity of literature in the second half of the twentieth century. Particular attention is paid to fragmentation, genre hybridity, intertextuality, irony, self-reflexivity, narrative decentering, and the crisis of the integral subject. It is argued that in postmodern literature form ceases to function merely as a vehicle of content and becomes an autonomous sphere of meaning production. The study also analyzes narrative organization, chronotope, and the role of the reader in the interpretive process. It is concluded that the poetics of the postmodern text is grounded in the dismantling of traditional assumptions about artistic unity, generic stability, and semantic finality. The article also notes the typological proximity between certain features of postmodern poetics and the aesthetics of decadence.